Lexias sexistas e violência política de gênero no twitter - Fontes, Ana Angélica Melo (2023)
This is a study on how violence against women is linguistically manifested from the gender bias observed in the Brazilian political scene, reverberated in cyberspace, through posts and interactions on the social network Twitter with the aim of offending such women. The investigation was based on the collection of tweets directed at the four candidates for the position of president of the republic of Brazil, in the 2022 election, the analysis was carried out between the months of August and December 2022.Based on gender theories and the categories proposed by Peres (2012), a lexical (lexicological) analysis was made of offensive and sexist words against women candidates for the Presidency in 2022, regarding the form of manifestation, the type of offense, to the sender's gender, type of speech act, grammatical class, lexical marking, type of utterance, presence/absence of graphic, phonetic or morphological marks, origin, presence/absence of superlativization. Preliminary quantitative results showed that words predominate in relation to expressions; moral offense, followed by inferiority; second-person direct attacks; words not lexically marked as offensive or pejorative in the dictionary. It was observed, in general, what other studies attested to: a tendency for offenses to attribute domestic roles to women, seeking to restrict their space of action, reduce their public competence and silence their voice, which manifested itself in five well-defined semantic fields. delimited and recurrent: domestic chores, female submission, falsehood, intellectual disability and mental disorder. The research also offers, as a result of the systematization of these data, a lexicographical product, which is the glossary of dysphemisms against women.